Perfluoropolyether carboxylic acids (novel alternatives to PFOA) impair zebrafish posterior swim bladder development via thyroid hormone disruption. (January 2020) - Wang, Jinxing; Shi, Guohui; Yao, Jingzhi; Sheng, Nan; Cui, Ruina; Su, Zhaoben; Guo, Yong; Dai, Jiayin
Highlights: Uninflated swim bladders was the most frequently malformation after PFECAs exposure. Toxicity increased in the order: PFO5DoDA > PFO4DA > PFOA > PFO3OA. Similar to PFOA, PFECA exposure lowered T3 and T4 levels in the larvae at 5 dpf. The transcription level of ugt1ab related to TH metabolism increased dose-dependently. T3 or T4 supplementation partly rescued PFECA-induced swim bladder malformation. Abstract: Perfluoropolyether carboxylic acids (PFECAs, CF3 (OCF2 )n COO −, n = 2–5) are novel alternatives to perfluorooctanoic acid (PFOA) and are widely used in industrial production. However, although they have been detected in surface water and human blood, their toxicities on aquatic organisms remain unknown. We used zebrafish embryos to compare the developmental toxicities of various PFECAs (e.g., perfluoro (3, 5, 7-trioxaoctanoic) acid (PFO3OA), perfluoro (3, 5, 7, 9-tetraoxadecanoic) acid (PFO4DA), and perfluoro (3, 5, 7, 9, 11-pentaoxadodecanoic) acid (PFO5DoDA)) with that of PFOA and to further reveal the key events related to toxicity caused by these chemicals. Results showed that, based on half maximal effective concentrations (EC50 ), toxicity increased in the order: PFO5DoDA > PFO4DA > PFOA > PFO3OA, with uninflated posterior swim bladders the most frequently observed malformation. Similar to PFOA, PFECA exposure significantly lowered thyroid hormone (TH) levels (e.g., T3 (3, 5, 3′-L-triiodothyronine) and T4 (L-thyroxine)) in the whole body of larvae at 5 d post-fertilization following disrupted TH metabolism. In addition, the transcription of UDP glucuronosyltransferase 1 family a, b ( ugt1ab ), a gene related to TH metabolism, increased dose-dependently. Exogeneous T3 or T4 supplementation partly rescued PFECA-induced posterior swim bladder malformation. Our results further suggested that PFECAs primarily damaged the swim bladder mesothelium during early development. This study is the first to report on novel emerging PFECAs as thyroid disruptors causing swim bladder malformation. Furthermore, given that PFECA toxicity increased with backbone OCF2 moieties, they may not be safer alternatives to PFOA.